Combination of bendamustine and rituximab as front-line therapy for patients with chronic lymphocytic leukaemia: multicenter, retrospective clinical practice experience with 279 cases outside of controlled clinical trials. (June 2016) - Gentile, Massimo; Zirlik, Katja; Ciolli, Stefania; Mauro, Francesca R.; Di Renzo, Nicola; Mastrullo, Lucia; Angrilli, Francesco; Molica, Stefano; Tripepi, Giovanni; Giordano, Annamaria; Di Raimondo, Francesco; Selleri, Carmine; et al.
Abstract: Recently, encouraging results in terms of safety and efficacy have been obtained using bendamustine–rituximab (BR) in untreated chronic lymphocytic leukaemia (CLL) patients enrolled in a phase II study. Here, we report a retrospective international multicenter study of CLL patients treated with BR as front-line therapy. The cohort included 279 patients with progressive CLL from 33 centers (29 Italian, 3 Israeli and 1 German) who received at least 1 cycle of BR as first-line treatment during the 2008–2014 period. The primary objective of this study was to evaluate the efficacy and safety of BR administered as front-line therapy, outside of controlled clinical trials. Median age was 70 years (range, 43–86 years); 62.4% were males and 35.8% had Binet stage C. Forty-two patients (15.2%) were unfit (cumulative illness rating scale [CIRS] score ≥7), and 140 (50.2%) had creatinine clearance ≤70 ml/min. Fluorescent in situ hybridisation analysis, available for 192 cases, showed that 21 (10.9%) had del11q and 18 (9.4%) del17p. The overall response rate (ORR) was 86.4%, with a complete remission rate of 28%. Patients with del17p had an ORR of 66.7%. After median follow-up of 24 months, the 2-year progression-free survival (PFS) was 69.9%; CIRS ≥7, immunoglobulin heavy-chain variable-region ( IGHV ) unmutated status, del17p and BR dose intensity <80% were independently associated with shorter PFS. Grade III or IV neutropenia, thrombocytopenia, and anaemia were observed in 25.9%, 15.4%, and 15.1% of patients, respectively. Twenty-four patients (8.6%) had severe infections. BR is also an effective and safe regimen for untreated CLL patients, outside of controlled clinical trials. Highlights: Until now, only three prospective trials showed the safety and efficacy of bendamustine–rituximab (BR) in previously untreated patients with chronic lymphocytic leukaemia (CLL). The present study is the first to assess safety and efficacy of BR in a large cohort of patients with untreated CLL, outside of controlled clinical trials. The results of our BR 'real-life' experience study are in good agreement with those obtained in three prospective primary studies, although some differences in terms of safety were evident. Thus, it seems that BR also achieves similar results in terms of outcome end-points in previously untreated CLL patients outside of controlled clinical trials.